2018
DOI: 10.1088/1361-648x/aaa3ac
|View full text |Cite
|
Sign up to set email alerts
|

Underscreening in ionic liquids: a first principles analysis

Abstract: An attempt is made to understand the underscreening effect, observed in concentrated electrolyte solutions or melts, on the basis of simple, admittedly crude models involving charged (for the ions) and neutral (for the solvent molecules) hard spheres. The thermodynamic and structural properties of these 'primitive' and 'semi-primitive' models are calculated within mean spherical approximation, which provides the basic input required to determine the partial density response functions. The screening length [For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
79
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 29 publications
15
79
1
Order By: Relevance
“…It must be stressed, however, that the Casimir force reported here is not directly related to the "underscreening" phenomenon discovered recently in experiments [13][14][15][16][17]. Note that the "first principles" theory of this phenomenon [18] is based on the same microscopic model and on the same theoretical tools employed in this paper. The present calculations of the Casimir force can be readily extended to asymmetric electrolytes (ions of different valences and diameters), as well as to models of ionic solutions with explicit solvent [18], within the same theoretical framework presented in Sections II and III.…”
Section: Discussionmentioning
confidence: 65%
“…It must be stressed, however, that the Casimir force reported here is not directly related to the "underscreening" phenomenon discovered recently in experiments [13][14][15][16][17]. Note that the "first principles" theory of this phenomenon [18] is based on the same microscopic model and on the same theoretical tools employed in this paper. The present calculations of the Casimir force can be readily extended to asymmetric electrolytes (ions of different valences and diameters), as well as to models of ionic solutions with explicit solvent [18], within the same theoretical framework presented in Sections II and III.…”
Section: Discussionmentioning
confidence: 65%
“…Recently, Gavish et al [42] and Rotenberg et al [43] suggested alternative theoretical explanations of the underscreening effect. Their arguments were based, respectively, on the phenomenological density-functional approach and the mean-spherical approximation.…”
Section: Nature Of Compacity and Overscreening Vs Underscreeningmentioning
confidence: 99%
“…However, since this elegant picture is based on defects in the crystalline state, which occurs for aqueous NaCl solutions above 6 M [38], while the experiments show an increase in the screening length even around 1 M, the understanding of the fluid state is still incomplete. The scaling law has motivated several other recent theoretical works [39][40][41], but has not yet been fully understood. While these works rely on different assumptions and yield slightly different results, all of them introduce in a similar way some non-Coulomb short-range interactions between the ions (and possibly, the solvent).…”
Section: Introductionmentioning
confidence: 99%